CEG-0598, a novel dual inhibitor of EGFR and C5aR demonstrates in vitro anticancer and antimetastatic activity in prostate cancer cells - Ayed A. Dera; Majed Al Fayi (Discover Oncology)
Abstract Background The EGFR is abundantly expressed in prostate cancer (PC). The anaphylatoxin C5a induces leukocyte migration via the C5a receptor (C5aR) by releasing matrix metalloproteinases (MMP) to favor metastasis in the tumor microenvironment. This work aims to selectively inhibit the EGFR and C5aR in PC cells to abort cell growth/ proliferation and metastasis. Methods For lead identification, high-throughput virtual screening (HTVS) of the ChemBridge library was followed by protein–ligand interaction profilers, GROMACS, and GMX-MMPBSA techniques. LNCaP and PC3 cells were used to validate in vitro efficacy. Results HTVS identified CEG-0598 with favorable binding affinities of − 10.2 kcal/mol and − 13.5 kcal/mol towards EGFR and C5aR respectively. Molecular dynamic simulations demonstrated stable binding interactions for CEG-0598 with Root Mean Square Deviation values around 0.06 nm. The ΔG binding calculation was − 50.29, and − 51.64 for EGFR and C5aR respectively. ADME supported favorable small molecule characteristics and selective inhibition profiles. Kinome-wide off-target virtual screening predicted EGFR to have above-average docking scores. CEG-0598 inhibited EGFR and C5aR activities with IC50 values of 145.8 nM and 55.51 nM respectively. The compound effectively controlled the proliferation of LNCaP and PC3cells with GI50 values of 156.1 nM, and 112.2 nM respectively. CEG-0598 prompted dose-responsive apoptosis in the PC cells and decreased the tarns endothelial migration of both PC cells. Treatment with CEG-0598 reduced the C5a-induced MMP activity in the LNCaP and PC3cells. Conclusion CEG-0598 is a selective EGFR/C5a dual inhibitor that downregulates MMP activity to control proliferation, migration and induce apoptosis, in PC cells warranting further preclinical developments.